PROCESSES AND RESULTS FROM IMPLEMENTING A JOINT VENTURE: CASE STUDY OF A SECTOR METAL-MECHANICAL COMPANY - Milan, Gabriel Sperandio (2016)
This research has sought to analyze processes and results from implementing the joint venture JOST Brasil Sistemas Automotivos Ltda., the result of a partnership between the Brazilian company Randon S/A. and the German company JOST-Werke. As research methodology, the qualitative approach was used from the development of a case study, through document analysis and in-depth interviews. Among the results, it possible to identify that the design and development of the joint venture was founded by interdependence, trust and commitment levels, quality of interactions, adequacy of governance mechanisms and congruence of goals between the parts.